Memoria y prácticas docentes: enseñanza de la violencia política peruana en un colegio público-emblemático peruano (Revista Peruana de Investigación Educativa, 2021)
Teaching a country’s recent history, constituted by dictatorships and internal conflicts, is a complex task for the educational institution. In Peru, the political violence of the 1980-2000 years is part of its recent history. The education system and its teachers, who were affected and remember that period, are currently teaching political violence in the Social Science courses of 5th grade.This sociology thesis seeks to understand the way in which four teachers of a public school-emblem of Metropolitan Lima teach the period of political violence, from their professional performance, the narratives they convey and their relationship with the social memories in conflict. The qualitative methodology used, triangulated class observations, in-depth interviews and document review. The theoretical approaches selected for the analysis were the sociology of school experience, memory and history, and types of professional performance. The results indicate that teaching about memory is interweaved by conflicts and discussions around the institutional and political context, educational dynamics in the classroom, and professional and personal trajectories of teachers.
Keywords: Memory and Teaching Practices: The Teaching of Peruvian Political Violence in A Public-Emblematic Peruvian School